(Re)discovering Street A in Nea Paphos, Cyprus. Results of Trial Trench III at Maloutena (season 2021) - Michał Michalik; Małgorzata Kajzer; Urszula Wicenciak; Jerzy Oleksiak; Kamila Niziołek; Ewdoksia Papuci-Władyka (Polish Archaeology in the Mediterranean)
This paper discusses data from excavations at Trial Trench III, set in the western part of the Villa of Theseus in Nea Paphos, Cyprus. The study aims to reconsider the diachronic development of Street A, located at the site of Maloutena, based on the results of stratigraphic analysis correlated with a typological study of collected pottery assemblages. More than 15000 pottery fragments representing a chronology ranging from the Late Classical (4th century BC) to the Byzantine period (7th century AD) were examined in their stratigraphic contexts in order to clarify the sequence observed during the excavations. As a result, it was possible to distinguish three phases of site development: Early Hellenistic, Middle Hellenistic, and Early Roman, followed by a phase related to robbing activity dated to the Byzantine period, and the final phase associated with natural processes on the abandoned site. This approach has allowed to correlate the new stratigraphic research results with previous knowledge about Maloutena as well as to challenge prior assumptions about its early history — in particular, those pertaining to the establishment of Street A and the first use of the Hellenistic street grid in the area.